Very severe spinal muscular atrophy (Type 0) - Dakhoul, Suleiman Al (Avicenna Journal of Medicine, 2017)
This case report describes a rare phenotype of very severe spinal muscular atrophy (SMA) in a newborn who presented with reduced fetal movements in utero and significant respiratory distress at birth. The patient was homozygously deleted for exon 7 and exon 8 of the survival motor neuron gene 1. Very severe SMA should be considered in the differential diagnosis of respiratory distress at birth, and more research should be dedicated to investigate the genetic determinants of its widely variable phenotypes.
Keywords: Exon; neurodegenerative; newborn; severe; spinal muscular atrophy